2012
DOI: 10.11646/zootaxa.3182.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater planarians (Platyhelminthes, Tricladida) from the Palearctic section of the African continent: new records, with the description of a new species

Abstract: On the basis of extensive surveys, an update is provided on the diversity, taxonomy, anatomy, and geographic distributionof five species of North African freshwater planarians, including the description of one new species. The new species Dug-esia tubqalis Harrath & Sluys, sp. nov. is mainly characterized by the following features: an elongated penis surroundedwith two penial folds at its base, the dorsal one bigger than the ventral ; an atrium divided into a male and common atriumby a kind of non-muscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 918 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, such a constriction occurs not only in S. nova but also in S. lugubris , S. polychroa , and S. mediterranea (cf. Luther, ; Figure 4; Harrath, Charni, Sluys, Zghal, & Tekaya, ; Figure 1; Harrath et al., , Figure 6).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, such a constriction occurs not only in S. nova but also in S. lugubris , S. polychroa , and S. mediterranea (cf. Luther, ; Figure 4; Harrath, Charni, Sluys, Zghal, & Tekaya, ; Figure 1; Harrath et al., , Figure 6).…”
Section: Resultsmentioning
confidence: 96%
“…These welldeveloped papillae or nipples are unique to S. nova, albeit that occasionally specimens of S. polychroa may show the anterior nipple, but then only weakly developed (cf. Harrath et al, 2012, Figure 6).…”
Section: Comparative Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although stygobiont freshwater triclads have received a good deal of attention (cf. Gourbault, , and references therein), many more studies have been published on planarians from epigean freshwaters, which have been extensively studied from all over the world (Sluys, Kawakatsu & Winsor, ; Sluys et al ., ; Lazaro et al ., ; Harrath et al ., ; Harrath et al ., ; Stocchino, Sluys & Manconi, ; Sluys, Kawakatsu & Timoshkin, ; Álvarez‐Presas & Riutort, ).…”
Section: Introductionmentioning
confidence: 99%
“…D. sicula was subsequently found on the islands of Elba [ 2 ] and Mallorca [ 3 ]. None of the originally described sexual populations can be currently found [ 4 ]; but, some sexual populations in northern Africa (Tunisia and Algeria) have been recently reported [ 5 - 7 ]. Moreover, a molecular-based study [ 8 ] showed that most of the numerous fissiparous populations of genus Dugesia present in the western Mediterranean belong to D. sicula .…”
Section: Introductionmentioning
confidence: 99%